A New Appraisal of Sri Lankan BB Zircon as a Reference Material for LA‐ICP‐MS U‐Pb Geochronology and Lu‐Hf Isotope Tracing. Issue 3 (20th April 2017) - Santos, Maristella M.; Lana, Cristiano; Scholz, Ricardo; Buick, Ian; Schmitz, Mark D.; Kamo, Sandra L.; Gerdes, Axel; Corfu, Fernando; Tapster, Simon; Lancaster, Penelope; Storey, Craig D.; Basei, Miguel A.S.; et al.
Abstract : A potential zircon reference material (BB zircon) for laser ablation‐inductively coupled plasma‐mass spectrometry (LA‐ICP‐MS) U‐Pb geochronology and Hf isotope geochemistry is described. A batch of twenty zircon megacrysts (0.5–1.5 cm 3 ) from Sri Lanka was studied. Within‐grain rare earth element (REE) compositions are largely homogeneous, albeit with some variation seen between fractured and homogeneous domains. Excluding fractured cathodoluminescence bright domains, the variation in U content for all analysed crystals ranged from 227 to 368 μg g −1 and the average Th/U ratios were between 0.20 and 0.47. The Hf isotope composition (0.56–0.84 g/100 g Hf) is homogeneous within and between the grains – mean 176 Hf/ 177 Hf of 0.281674 ± 0.000018 (2 s ). The calculated alpha dose of 0.59 × 10 18 g −1 for a number of BB grains falls within the trend of previously studied, untreated zircon samples from Sri Lanka. Aliquots of the same crystal (analysed by ID‐TIMS in four different laboratories) gave consistent U‐Pb ages with excellent measurement reproducibility (0.1–0.4% RSD). Interlaboratory assessment (by LA‐ICP‐MS) from individual crystals returned results that are within uncertainty equivalent to the TIMS ages. Finally, we report on within‐ and between‐grain homogeneity of the oxygen isotope systematic of four BB crystals (13.16‰ VSMOW). Key Points: A new matrix‐matched zircon reference material was developed for U‐Pb and Hf analyses. The material comes from a large ( 300 g) batch of 0.5–1.5 cm³ crystals. The material is available to researchers using LA‐ICP‐MS and other in situ techniques.